Relationship between extrinsic factors and the acromio-humeral distance. (June 2016) - Mackenzie, Tanya Anne; Herrington, Lee; Funk, Lenard; Horsley, Ian; Cools, Ann
Abstract: Background: Maintenance of the subacromial space is important in impingement syndromes. Research exploring the correlation between biomechanical factors and the subacromial space would be beneficial. Objectives: To establish if relationship exists between the independent variables of scapular rotation, shoulder internal rotation, shoulder external rotation, total arc of shoulder rotation, pectoralis minor length, thoracic curve, and shoulder activity level with the dependant variables: AHD in neutral, AHD in 60° arm abduction, and percentage reduction in AHD. Design: Controlled laboratory study. Method: Data from 72 male control shoulders (24.28years STD 6.81 years) and 186 elite sportsmen's shoulders (25.19 STD 5.17 years) were included in the analysis. The independent variables were quantified and real time ultrasound was used to measure the dependant variable acromio-humeral distance. Results: Shoulder internal rotation and pectoralis minor length, explained 8% and 6% respectively of variance in acromio-humeral distance in neutral. Pectoralis minor length accounted for 4% of variance in 60° arm abduction. Total arc of rotation, shoulder external rotation range, and shoulder activity levels explained 9%, 15%, and 16%–29% of variance respectively in percentage reduction in acromio-humeral distance during arm abduction to 60°. Conclusion: Pectorals minor length, shoulder rotation ranges, total arc of shoulder rotation, and shoulder activity levels were found to have weak to moderate relationships with acromio-humeral distance. Existence and strength of relationship was population specific and dependent on arm position. Relationships only accounted for small variances in AHD indicating that in addition to these factors there are other factors involved in determining AHD. Highlights: Pectorals minor length had a moderate relationship with AHD. Shoulder rotation ranges had a weak relationship with AHD. Shoulder activity levels had a moderate relationships with AHD. Existence and strength of relationship was population specific. Relationships only accounted for small variances in AHD.